Framework analítico de governanças em áreas marinhas protegidas: abordagens teórica e empírica - Silva, Manuela Dreyer da (2019)
Marine protected areas have emerged on the mainstream of strategies for biodiversity conservation worldwide. They comprise geographical spaces in which the use of natural resources is regulated by institutional mechanisms (centered on the state or from other arrangements such as adaptive co-management), in order to achieve the maintenance of ecosystem services, resources, and cultural values. The governance models present in Brazilian MPAs are otherwise frequently based on hierarchical standards, which ignore important social variables and compromise effective social participation. This research has worked with the reality of artisanal fishing from the perspective of interactive governance and actor-network theory (ANT) in the Paranaguá Estuarine Complex (CEP), in particular in three MPAs: the Guaraqueçaba Environmental Protection Area, the Ecological Station of Guaraqueçaba and the Superagui National Park. These perspectives discuss other organizational models, based on the complexity of the socioecological (SES) and sociotechnical (STS) systems. The thesis of this study is based on this reading: an analysis of interactive governance based on ANT principles can overcome the problem of fragmented readings between the governing system and the system to be governed in MPAs. To test this thesis, the general objective of the research was to propose a framework for the analysis of MPA governance, connecting existing notions of SES and STS, based on this re-reading of interactive governance and based on the study of the estuarine territory of the APA of Guaraqueçaba. In combining these approaches, the thesis intended to attribute to non-humans a more open sort of action than the traditional natural causality, considering that the associations perceived in the description of the network modify the governing interactions. Working with exploratory research and with mixed methods of analysis, this research (1) used content analysis as a methodological tool to define governance attributes (2) used experience in another country (Cuba) to define transformation vectors in governance; (3) described the sociotechnical network based on documental analysis and participant observation. As results, an important compilation of governance attributes was presented and discussed; vectors of transformation of the mode of governance were described, in a hierarchical governance gradient for self-government; and the ANT perspective was used to describe the network in MPAs. From this, it was possible to join socioecological and sociotechnical elements in a framework for governance analysis. The main implication of this structure was to combine, through the network perspective, the system of governance and the system to be governed, presenting vectors of transformation of the modes of governance. In this way, the thesis proved feasible. It is concluded, then, that the framework is able to point out incompatibilities that exist in the processes of governance, why some of these incompatibilities persist and what are the possibilities of transformation between modes of governance in an MPA with small-scale fisheries.